A novel cryptosystem based on DNA cryptography and randomly generated mealy machine. Issue 104 (May 2021) - Pavithran, Pramod; Mathew, Sheena; Namasudra, Suyel; Lorenz, Pascal
Abstract: Nowadays, the amount of data produced and stored in computing devices is increasing at an alarming rate. Tremendous amounts of critical and sensitive data are transmitted between all these devices. Thus, it is very imperative to guarantee the security of all these indispensable data. Cryptography is a commonly used technique to ensure data security. The fundamental objective of cryptography is to transmit data from the sender to the receiver in the most secure way, so that an attacker is unable to extract the original data content. This paper proposes a novel cryptosystem based on Deoxyribonucleic Acid (DNA) cryptography and finite automata theory. The system is made of three entities, namely a key pair generator, a sender and a receiver. The sender generates a 256-bit DNA based secret key based on the attributes of the receiver, and this key is used for data encryption. Then, a randomly generated Mealy machine is used for coding the DNA sequence, which makes the ciphertext more secure. The proposed scheme can protect the system against numerous security attacks, such as brute force attack, known plaintext attack, differential cryptanalysis attack, cipher text only attack, man-in-the-middle attack and phishing attack. The results and discussions show that the proposed scheme is efficient and secure than the existing schemes.